Combined heat and power [compact disc] : cost effectiveness, prospects and technology for Malaysia pulp and paper industry - 435203 Fadhlillah Adnan (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2006